Effect of a Spacer Group on Surface Activity, Salinity and Hardness Tolerance, Mimic Oil Washing Efficiency of Monododecyl Diaryl Disulfonate. Issue 1 (28th February 2013) - Xing, Fengmei; Niu, Jinping; Liu, Xiaochen; Wang, Xiaoyu
Abstract: Three anionic surfactants of the monododecyl diaryl disulfonate type (MDDADS‐n, n = 0, 1, 2) were synthesized. The structural characters of MDDADS‐n surfactants were verified by electrospray ionization/mass spectrometry. The effect of the spacer group on the surface activity, salinity and hardness tolerance and mimic oil washing efficiency were investigated. The results showed that the critical micelle concentration (CMC), surface tension at CMC, C20 and the minimum area per molecule of the anionic surfactants increased when the spacer group length increased. There was less effect on mimic oil washing efficiency of MDDADS‐n when the spacer group changed; meanwhile, they displayed higher mimic oil washing efficiency in salt solution (NaCl or CaCl2 ) than that of sodium dodecylbenzenesulfonate (SDBS); all MDDADS‐n surfactants showed much lower sensitivity to water hardness than SDBS, what would be beneficial to enhancing oil recovery in a high salinity oil field.